C-Reactive Protein as a Therapeutic Target in Age-Related Macular Degeneration - Molins, Blanca; Romero-Vázquez, Sara; Fuentes-Prior, Pablo; Adan, Alfredo; Dick, Andrew D. (Frontiers in Immunology, 2018)
Age-related macular degeneration (AMD), a retinal degenerative disease, is the leading cause of central vision loss among the elderly population in developed countries and an increasing global burden. The major risk is ageing, compounded by other environmental factors and association with genetic variants for risk of progression. Although the etiology of AMD is not yet clearly understood, several pathogenic pathways have been proposed, including dysfunction of the retinal pigment epithelium, inflammation, and oxidative stress. The identification of AMD susceptibility genes encoding complement factors and the presence of complement and other inflammatory mediators in drusen, the hallmark deposits of AMD, support the concept that local inflammation and immune-mediated processes play a key role in AMD pathogenesis that may be accelerated through systemic immune activation. In this regard, increased levels of circulating C-reactive protein (CRP) have been associated with higher risk of AMD. Besides being a risk marker for AMD, CRP may also play a role in the progression of the disease as it has been identified in drusen, and we have recently found that its monomeric form (mCRP) induces blood retinal barrier disruption in vitro. In this review, we will address recent evidence that links CRP and AMD pathogenesis, which may open new therapeutic opportunities to prevent the progression of AMD.